Pengaruh Intensitas Cahaya Led dan Macam Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Basil (Ocimum Basilicum L.) Indoor Hidroponik Wick Sistem - Hisam, Mohamad Hisam Fachrudin; Santoso , Juli; Hidayat , Ramdan (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background:The basil plant (Ocimum basilicum L.) is characterized by its mint-like aroma and fresh taste, but its cultivation is still small and agricultural land is increasingly limited. This problem can be overcome by indoor hydroponic cultivation using artificial lights. The research was carried out in Ngagel Rejo Utara No. 24, Surabaya City, East Java from October-November 2022 using artificial LED light installations in closed rooms.Method: This research is a factorial experiment which was prepared using a Split Plot Design (RPT) which consisted of two factors and was repeated three times. The first factor is the intensity of LED light (C) as the main plot which consists of 4 treatment levels, namely 1,500 lux (C1), 1,700 lux (C2), 2,000 lux (C3), 2,200 lux (C4) and the second factor is the type of planting medium ( M) as a subplot consists of 3 treatment levels, namely charcoal husk (M1), cocopeat (M2), rockwool (M3).Results: The results of the research showed that the combined treatment of light intensity of 2,200 lux and rockwool planting media was able to increase the parameters of plant height, number of leaves, wet stover weight, dry stover weight and the volume of nutrient absorption by the plants.Conclusion: The combination of 2,200 lux light intensity treatment and rockwool planting media is the best combination for the parameters of plant height, number of leaves, wet stover weight, dry stover weight and the volume of nutrient uptake of basil plants (Ocimum basilicum L.) indoor hydroponic wick system.